Toxoplasma gondii EN VICUÑAS DE LA RESERVA NACIONAL DE PAMPA GALERAS - Zuzunaga D., Mijail (2012)
The definitive host of the protozoan Toxoplasma gondii is the feline and intermediate hosts are a wide number of species, such as sheep, goats, pigs, birds and human. This protozoan is worldwide distributed, has zoonotic connotations, and cause reproductive problems in livestock, especially in sheep. The objective of the present study was to determine the seroprevalence of T. gondii in vicunas at the National Reserve of Pampa Galeras, located inAyacucho, Peru.Atotal of 191 vicunas, both males and females, were blood sampled and serum was analyzed by the indirect immunofluorescent antibody test (IFAT). The resulting seroprevalence was 5.8 ± 3.3%, without statistical differences due to sex and age factors. The present study demonstrated the presence of T. gondii infection for in vicunas of theNational Reserve of Pampa Galeras.